Paper‐based Wearable Electrochemical Sensors: A New Generation of Analytical Devices - Deroco, Patricia Batista; Wachholz Junior, Dagwin; Kubota, Lauro Tatsuo (Electroanalysis (New York, N.Y.), 2023)
Over the past few years, the emergence of electrochemical wearable sensors has attracted considerable attention because of their promising application in point‐of‐care testing due to some features such as high sensitivity, simplicity, miniaturization, and low fabrication cost. Recent developments in new fabrication approaches and innovative substrates have resulted in sensors able to real‐time and on‐body measurements. Wearable electrochemical sensors have also been combined with paper‐based substrates and directly used on human skin for different applications for non‐invasive analyses. Furthermore, wearable electrochemical sensors enable monitoring analytes in different biofluids without complex procedures, such as pre‐treatment or sample manipulation. The coupling of IoT to various wearable sensors has also attracted attention due to real‐time data collection and handling in remote and resource‐limited conditions. This mini‐review presents the significant advances in developing wearable electrochemical devices, such as sampling, data collection, connection protocols, and power sources, and discusses some critical challenges for higher performance in this field. We also present an overview of the application of paper as an intelligent substrate for electrochemical wearable sensors and discuss their advantages and drawbacks. Lastly, conclude by highlighting the future advances in wearable sensors and diagnostics by coupling real‐time and on‐body measurements to multiplexed detection of different biomarkers simultaneously, reducing the cost and time of classical analysis to provide fast and complete overall physiological conditions to the wearer.